Hubungan Antara Asupan Lemak, Asupan Serat Dan Status Gizi Terhadap Siklus Menstruasi Remaja Kelas X Dan XI Di SMA Muhammadiyah 1 Surakarta - NABILA, Nabila, Fitriana Mustikaningrum, S.Gz, M.Sc, Rully Sudaryanto S. SiT (2015)
Introduction: Menstruation happen between 6-10 years old, usually 12 years old. Menstruation cycle that irregular was normally when it is happen during the first twenty years before the first menstruation. Fat intake and nutrition status correlation with changes in hormone steroid value that factor in the proccess of setting menstruation cycle. Objective: The purpose of this research is to know corelation between fat intake, fiber intake and nutrition status for menstruation cycle for teenagers class X and XI at SMA MUHAMMADIYAH 1 SURAKARTA. Research method: This research used observational with crossectional approach. Sample used was a student class X and XI at SMA MUHAMMADIYAH 1 SURAKARTA that has menstruation. Taking sample with proportional random sampling. Menstruation cycle can obtain with questioners while fiber intake and fat used food frequency semi quantitative (ffq) method. Results: This research showed that more than half of the study subjects with irregular menstrual cycles have fat intake more categories, which is 59.3 %, with p = 0.710. More than half of the study subjects with regular menstrual cycles have good fiber intake category, which is 60 %, with p = 0.326. And More than half of the study subjects with irregular menstrual cycles have more nutrition status, which is 88.2 %, with p = 0.03. Conclusion: No corelation fat intake and fiber intake with menstruation cycle at SMA Muhammadiyah 1 Surakarta. Any corelation nutrition status with menstruation cycle at SMA Muhammadiyah 1 Surakarta.